Modification and characterization of microwave assisted interstitial N-doped Ti0₂ for photodegradation of RR4 dye / Mohammad Saifulddin Mohd Azami - Mohd Azami, Mohammad Saifulddin (2017)
Mostly, researchers were prepared nitrogen doped titanium dioxide (N-doped T1O2) using chemical preparation such as solvothermal, ion implantation, sol-gel, calcination, sonochemical and sputtering technique and this method are very complicated due to the process either using specific equipment or consumed chemical to dissolved the precursor. The preparations N-doped Ti02 under microwave treatment was also conducted using sol gel method. Fewer works exploited by using solid state method and most of them was prepared N-doped Ti02 under muffle furnace. Therefore, no study focused on the modification N-doped TiCh using commercially available TiCh under microwave. Thus, an interstitial N-doped TiCh has been synthesized under microwave irradiation using urea as nitrogen precursor and commercially available P25-Ti02. The preparation N-doped TiCh was undergoes solid state method with contributed to the formation of interstitial, which is in contrast to other solid state methods that give substitutional N-doped TiCh. The various ratio of Ti02 and urea was mixed using mechanical mixing and heating under microwave irradiation using various irradiation power. The optimization study was applied under photodegradation of Reactive Red 4 (RR4) dye for 50 min under 55-W fluorescent lamp. The comparison study was done by comparing with different irradiation light (visible and solar irradiation) and comparing with immobilization technique using Double Sided Adhesive Tape (DSAT) technique.The optimum modified N-doped TiCh found at 3 g urea in 7 g Ti02 denoted as U3-800 prepared at 800 W of microwave irradiation under 30 min constant time. It was observed that N has chemically bonded with titania producing interstitial Ti-O-N proven by X-ray Photoelectron Spectroscopy (XPS) analysis at 400.3 and 404.8 eV. The interstitial Ti-O-N also can be exposed by Fourier Transform Infrared Spectroscopy (FTIR) suggested as hyponitrite formation. There is no transformation phase occurred in U3-800 compared with unmodified TiC>2 in X-ray diffraction (XRD) analysis. The band gap energy (Eg) of the modified sample was ca. 2.9 eV as detected by UV/Vis DRS. Photodegradation rate of RR4 dye under U3-800 is 1.6 times faster in comparison with unmodified TiCh as well as control Ti02 under a normal 55-W fluorescent lamp. An active photo response for U3-800 sample under visible light irradiation observed with 80 min of time to complete RR4 color removal while no photocatalytic degradation detected from unmodified and control TiCh. Immobilization of the U3-800 sample was applied by using double sided adhesive tape (DSAT) as a thin layer binder and the photoactivity of immobilized U3-800 is comparable to the suspension mode. The immobilized U3-800 is durable and can continuously used for 30 cycles without affecting the photoactivity performance. This simple technique will make ease to industrial to prepare the modified TiC>2 and help the pre-treatment of industrial to degraded the pollutant in twenty-four hour. Moreover, this physical technique prepared N-doped TiCh was also promising the green technology and environmental friendly which successfully producing interstitial type N without using any solvent.